Service design as an innovation approach in technology startups: a longitudinal multiple case study. (16th May 2020) - Korper, Ana Kustrak; Patrício, Lia; Holmlid, Stefan; Witell, Lars
Abstract : While service design has been accepted as a human‐centered and cocreative approach to service innovation, its role in technology‐driven contexts, specifically technology startups, has been largely unexplored. Previous research suggests that technology startups tend to focus on technical aspects of innovation, neglecting the value cocreation potential of service innovation that service design can facilitate. Focusing on value propositions as the main mechanisms of service innovation, this study explores how service design facilitates service innovation in technology startups. This longitudinal study examines the opportunities and challenges of introducing service design for the purpose of service innovation in five technology startups over a period of 11 months. Results reveal how service design facilitates the creation of new value propositions that expand the previous technology‐driven focus towards a human‐centered and cocreative one. Additionally, findings suggest that there are two levels of how service design becomes embedded in technology startups that are contingent on their life cycle stage. This contributes to the service innovation literature that views innovation as development of new value propositions and describes the key role of service design. The study also discusses managerial implications of the findings for technology startups and service designers and provides directions for future research.